Seasonal variation in the foraging behavior of neotropical tyrant flycatchers (Tyrannidae) in a Cerrado fragment, Brazil. Issue 2 (4th March 2023) - Ferrari, Andrea; Motta-Junior, José C.; Siqueira, José de O.
Abstract : The foraging behavior of tyrant flycatchers (Aves Tyrannidae) is characterized by a stereotyped way of "search-and-capture" with subtle interspecific variations related to morphological and ecological factors. In this study, we quantified the foraging behavior of Cock-tailed tyrant ( Alectrurus tricolor ), Streamer-tailed tyrant ( Gubernetes yetapa ), Gray monjita ( Nengetus cinereus ), and White-rumped monjita ( Xolmis velatus ) in the dry and wet seasons to determine whether these species use foraging maneuvers, search time and the distances moved from one unsuccessful perch to a new perch (give-up flight) in different proportions between the 2 seasons. We also studied whether the foraging behavior of Cock-tailed tyrant is influenced by the sex and age of the individual. Our results indicated the birds change their behavior between the dry and wet seasons. Aerial hawking was predominantly used by Cock-tailed tyrant and Streamer-tailed tyrant during both seasons, but by White-rumped monjita only during the wet season. Perch-to-ground was the predominant hunting strategy for Gray monjita during both seasons and for White-rumped monjita during the dry season. We found Cock-tailed tyrant and White-rumped monjita covered greater distances during the wet season, when environmental conditions are more favorable, which may be related to breeding requirements.